Beyond rules: How institutional cultures and climate governance interact. (28th September 2021) - Bremer, Scott; Glavovic, Bruce; Meisch, Simon; Schneider, Paul; Wardekker, Arjan
Abstract: Institutions have a central role in climate change governance. But while there is a flourishing literature on institutions' formal rules, processes, and organizational forms, scholars lament a relative lack of attention to institutions' informal side; their cultures. It is important to study institutions' cultures because it is through culture that people relate to institutional norms and rules in taking climate action. This review uncovers what work has been done on institutional cultures and climate change, discerns common themes around which this scholarship coheres, and advances and argument for why institutional cultures matter. We employed a systematic literature review to assemble a set of 54 articles with a shared concern for how climate change and institutional cultures concurrently affect each other. The articles provided evidence of a nascent field, emerging over the past 5–10 years and fragmented across literatures. This field draws on diverse concepts of institutionalism for revealing quite different expressions of culture, and is mostly grounded in empirical studies. These disparate studies compellingly demonstrate, from different perspectives, that institutional cultures do indeed matter for implementing climate governance. Indeed, the articles converge in providing empirical evidence of eight key sites of interaction between climate change and institutional cultures: worldviews, values, logics, gender, risk acceptance, objects, power, and relationality. These eight sites are important foci for examining and effecting changes to institutions and their cultures; showing how institutional cultures shape responses to climate change, and how climate change shapes institutional cultures. This article is categorized under: The Social Status of Climate Change Knowledge > Knowledge and Practice Abstract : Institutional cultures mediate how people relate to institutions' rules in addressing climate change. We reveal eight sites of interaction between climate change and institutional cultures, where cultures affect how climate change is interpreted and taken up in institutions and are at the same time sites where institutional changes take place. Credit : Edgar Melitao.